AL-QUR’AN DAN KEARIFAN LOKAL BUDAYA JAWA: Studi Kaidah Tafsir Kitab Qawaid al-Hisan - Widodo Hami (Al-Nizam: Indonesian Journal of Research and Community Service, 2023)
Absttak: This research demonstrates the relationship between the Koran and local Javanese cultural wisdom. By using an interpretive rules approach, this article tries to explore the relevance between local Javanese cultural wisdom and the contents of the Koran. The method used in this research is descriptive analysis. This research resulted in findings that some Javanese traditions are relevant to the instructions of the Koran. By using an approach to the rules of interpretation that was pioneered by Shaykh Abdurrahman in the book Qawaid al-Hisan. Keywords: Local Wisdom, Javanese Culture, Interpretation Rules